Erythropoietin Exacerbates Inflammation and Increases the Mortality of Histoplasma capsulatum-Infected Mice - Gisele Aparecida Locachevic; Priscilla Aparecida Tartari Pereira; Adriana Secatto; Caroline Fontanari; Alyne Fávero Galvão; Morgana Kelly Borges Prado; Karina Furlani Zoccal; Tânia Petta; Luiz Alberto Beraldo Moraes; Simone Gusmão Ramos; Fabíola Attie de Castro; Carlos Artério Sorgi; et al. (Hindawi Limited, 2015)
Erythropoietin (EPO) is a key hormone involved in red blood cell formation, but its effects on nonerythroid cells, such as macrophages, have not been described. Macrophages are key cells in controlling histoplasmosis, a fungal infection caused by Histoplasma capsulatum (Hc). Considering that little is known about EPO's role during fungal infections and its capacity to activate macrophages, in this study we investigated the impact of EPO pretreatment on the alveolar immune response during Hc infection. The consequence of EPO pretreatment on fungal infection was determined by evaluating animal survival, fungal burden, activation of bronchoalveolar macrophages, inflammatory mediator release, and lung inflammation. Pretreatment with EPO diminished mononuclear cell numbers, increased the recruitment of F4/80+/CD80+ and F4/80+/CD86+ cells to the bronchoalveolar space, induced higher production of IFN-γ, IL-6, MIP-1α, MCP-1, and LTB4, reduced PGE2 concentration, and did not affect fungal burden. As a consequence, we observed an increase in lung inflammation with extensive tissue damage that might account for augmented mouse mortality after infection. Our results demonstrate for the first time that EPO treatment has a deleterious impact on lung immune responses during fungal infection.